Electromyographic validation of the trapezius and serratus anterior muscles in military press exercises with open grip - Büll, M. L. [UNESP]; Vitti, M.; Freitas, V.; Rosa, G. J. (Electromyogr Clin Neurophysiol, 2001)
It was studied the trapezius muscle and serratus anterior muscle in 24 male volunteers using a 2-channel TECA TE 4 electromyograph and Hewlett Packard surface electrodes, during the execution of four different modalities of military press exercises with open grip. The results showed that TS acted significantly in the modalities standing and sitting press behind neck, while SI acted in all the modalities, i.e., standing and sitting press behind neck and forward, justifying their inclusion as basic exercises for physical conditioning programmes.